Lactate oxidation at the mitochondria: a lactate-malate-aspartate shuttle at work - Kane, Daniel A. (Frontiers in Neuroscience, 2014)
Lactate, the conjugate base of lactic acid occurring in aqueous biological fluids, has been derided as a “dead-end” waste product of anaerobic metabolism. Catalyzed by the near-equilibrium enzyme lactate dehydrogenase (LDH), the reduction of pyruvate to lactate is thought to serve to regenerate the NAD+ necessary for continued glycolytic flux. Reaction kinetics for LDH imply that lactate oxidation is rarely favored in the tissues of its own production. However, a substantial body of research directly contradicts any notion that LDH invariably operates unidirectionally in vivo. In the current Perspective, a model is forwarded in which the continuous formation and oxidation of lactate serves as a mitochondrial electron shuttle, whereby lactate generated in the cytosol of the cell is oxidized at the mitochondria of the same cell. From this perspective, an intracellular lactate shuttle operates much like the malate-aspartate shuttle; it is also proposed that the two shuttles are necessarily interconnected. Among the requisite features of such a model, significant compartmentalization of LDH, much like the creatine kinase of the PCr shuttle, would facilitate net cellular lactate oxidation under a variety of conditions.